Early Adolescent MK-801 Exposure Impairs the Maturation of Ventral Hippocampal Control of Basolateral Amygdala Drive in the Adult Prefrontal Cortex - Thomases, Daniel R. (Society for Neuroscience, 2014)
The adolescent susceptibility to the onset of psychiatric disorders is only beginning to be understood when factoring in the development of the prefrontal cortex (PFC). The functional maturation of the PFC is dependent upon proper integration of glutamatergic inputs from the ventral hippocampus (vHipp) and the basolateral amygdala (BLA). Here we assessed how transient NMDAR blockade during adolescence alters the functional interaction of vHipp–BLA inputs in regulating PFC plasticity. Local field potential recordings were used to determine changes in long-term depression (LTD) and long-term potentiation (LTP) of PFC responses resulting from vHipp and BLA high-frequency stimulation in adult rats that received repeated injections of saline or the NMDAR antagonist MK-801 from postnatal day 35 (P35) to P40. We found that early adolescent MK-801 exposure elicited an age- and input-specific dysregulation of vHipp–PFC plasticity, characterized by a shift from LTD to LTP without altering the BLA-induced LTP. Data also showed that the vHipp normally resets the LTP state of BLA transmission; however, this inhibitory regulation is absent following early adolescent MK-801 treatment. This deficit was reminiscent of PFC responses seen in drug-naive juveniles. Notably, local prefrontal upregulation of GABA(A)α1 function completely restored vHipp functionality and its regulation of BLA plasticity in MK-801-treated rats. Thus, NMDAR signaling is critical for the periadolescent acquisition of a GABA-dependent hippocampal control of PFC plasticity, which enables the inhibitory control of the prefrontal output by the vHipp. A dysregulation of this pathway can alter PFC processing of other converging afferents such as those from the BLA.